Prevalence and predictors of metabolic syndrome in rheumatoid arthritis - Naik, Muzafar; Bhat, Tariq; Jalalie, Ummer; Ganayie, Mohd Tahir; Waseem, Mir; Bhat, Arif (International Journal of Research in Medical Sciences, 2017)
Background: Rheumatoid arthritis (RA) is associated with increased cardiovascular morbidity and mortality secondary to accelerated atherosclerosis. There is a strong association of metabolic syndrome (MS) with atherosclerosis. The objective of this study was to assess the prevalence of MS in RA and to identify the predictors of MS in RA. Methods: The study included 100 patients of RA (83 females,17 males; median age 42.5(17) years diagnosed according to 2010 American College of Rheumatology-European League Against Rheumatism classification criteria who were on treatment and 110 age and sex-matched apparently healthy controls (26 males, 84 females; median age 45 (20) years). The frequency of MS was assessed using joint consensus 2009 criteria. Patients were also assessed in terms of disease activity, using disease activity score 28 CRP. Logistic regression was used to identify predictors of MS in RA. Results: Metabolic syndrome was found in 45% of RA group and 22.7% of control group according to joint consensus 2009 criteria (p<0.005). RA group was significantly more likely to have low high-density lipoprotein (65%), elevated blood pressure (60%) levels and abnormal sugar (28%). In RA group, CRP (odds ratio: 1.101, confidence interval: 1.032-1.174 (p=0.004) adjusted for age, DAS 28 score & Anti-CCP remained independent predictor for presence of MS in RA. Conclusions: The frequency of MS was higher in RA group compared to control group. High CRP remained independent predictor associated with presence of MS. There was no association of high disease activity with MS in our RA patients. These findings suggest that the treating physician should screen RA patients early for presence of MS.